Isolation of a sleep-promoting compound from Polygonatum sibiricum rhizome - Jo, Kyungae (Food Sci Biotechnol, 2018)
The aim of this study was to identify sleep-promoting substance from Polygonatum sibiricum rhizome extract (PSE) with the regulation of sleep architecture. PSE showed a decrease in sleep latency time and an increase in the sleeping time. In the electroencephalography analysis of rats, PSE (150 mg/kg) showed an increase of non-rapid eye movement by 38% and a decrease of rapid eye movement by 31% compared to the control. This sleep-promoting activity was found to be involved in the GABA(A)-BDZ receptor. The chemical structure of the pure compound was determined by the (1)H and (13)C nuclear magnetic resonance spectroscopy and gas chromatography mass spectrometry analysis; active compound was glyceryl-1-monolinoleate. The commercial standard glyceryl-1-monolinoleate showed a similar inhibitory concentration on [(3)H]-flumazenil binding to GABA(A)-BDZ receptors with final active fraction of PSE. The results indicate that glyceryl-1-monolinoleate is a major active compound responsible for the PSE-derived sleep promotion.